Muslim Greetings: A Critical Analysis of Salafi Scholars' Views on Kneeling and Bending Etiquette in Islam - Gambari, Yusuph Dauda; Olayinka Ibrahim, Oniye (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This paper delves into the discourse surrounding traditional Islamic greetings, specifically focusing on the viewpoints of Salafi scholars regarding the practices of kneeling and bending as manners of greeting in Islam. Drawing upon a comprehensive review of primary sources, classical texts, and contemporary scholarly works, this study critically examines the arguments and interpretations presented by Salafiyyah scholars. It investigates the theological, cultural, and historical contexts shaping their perspectives on the appropriateness and religious significance of these greetings. Furthermore, the paper explores the implications of these viewpoints within the broader Islamic community and discusses potential avenues for inter-sectarian dialogue and understanding. By engaging with diverse scholarly viewpoints and contextualizing them within broader Islamic teachings, this analysis contributes to a nuanced understanding of greeting etiquettes in Islam and facilitates constructive discourse within the global Muslim community.